Seasonal Variation in Chemical Composition of Total Suspended Particles During the COVID-19 Pandemic in the Source Area of Urumqi River, Tianshan, China - Zheng, Cunying; Li, Zhongqin; Zhang, Xin; Jiang, Huimin; Zhou, Xi (Frontiers in Earth Science, 2022)
The research of atmospheric aerosol in mountain glacier areas has attracted more and more people's attention. For the first time, a field observation study of total suspended particles (TSPs) for four seasons from September 2019 to August 2020 was carried out at the Tianshan Glaciological Station in the source area of Urumqi River, East Tianshan Mountains, China. The seasonal variation characteristics and sources of carbonaceous composition (OC and EC) and water-soluble inorganic ions (WSIIs) were studied. The findings stated that the concentrations of TSPs presented typical seasonal characteristics of high in autumn and low in winter, with the annual average value of 181.4±169.7 μg m-3. OC, EC, Ca2+, SO42−, and NO3− were the predominant chemical components, with the highest average concentration in autumn. The concentration of SOC was higher in summer and autumn, especially in summer, indicating that secondary reactions were frequent in summer. The ratios of OC/EC, K+/EC indicated that carbonaceous components were mainly affected by fossil fuels combustion. The average ratio of NO3−/SO42− was 0.31±0.17, indicating that stationary source emissions were predominant. The Principal component analysis illustrated that aerosols were mainly affected by dust, coal combustion, and automobile exhaust. Results of HYSPLIT and PSCF indicated that the local sources made significant contributions to TSPs in the source of Urumqi River.